Graphite-micron-sized carbon black sphere composite carbon paste, electrode layer, preparation of graphite-micron-sized carbon black sphere composite carbon paste and electrode layer, and application of electrode layer in CPSC

The graphite-micro-scale carbon black ball composite carbon slurry is prepared by collaborative ball milling of nano-scale carbon black and micro-scale graphite sheets, which solves the problem that low-temperature mesoporous carbon electrodes are difficult to form appropriate pore structures, and achieves high-efficiency photoelectric conversion efficiency under low-temperature conditions.

CN119833203APending Publication Date: 2025-04-15CENT SOUTH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411985613.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing low-temperature mesoporous carbon electrodes are difficult to form appropriate pore structures in perovskite solar cells, which limits the improvement of photoelectric conversion efficiency.

Method used

By synergistically ball milling the nano-scale carbon black and micro-scale graphite sheets, a graphite-micro-scale carbon black ball composite carbon slurry is formed, and a carbon electrode layer with an appropriate pore structure is prepared.

Benefits of technology

The mesoporous three-dimensional carbon electrode layer was successfully constructed under low temperature conditions, which improved the photoelectric conversion efficiency of perovskite solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833203A_ABST
    Figure CN119833203A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of CPSC carbon paste, and particularly discloses graphite-micron-sized carbon black sphere composite carbon paste and preparation and application thereof.The preparation method comprises the steps that a solution system composed of nanoscale carbon black, micron-sized graphite flakes and a solvent is subjected to ball milling treatment, and carbon paste compounded with graphite-micron-sized carbon black spheres is obtained; wherein the weight ratio of the micron-sized graphite flake to the nano-sized carbon black is (1-4): 1; the size of a sheet layer of the micron-sized graphite sheet is 10 to 50 microns; the solvent is a solvent containing C1-C4 monohydric alcohol or water; the ball milling time is more than 10-40 hours. According to the method, the mesoporous three-dimensional carbon electrode layer adaptive to the mesoporous CPSC can be simply constructed under the condition of full low temperature of 150 DEG C or below, and the PCE and other properties of the mesoporous three-dimensional carbon electrode layer can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of solar cells, and in particular to the field of carbon electrode perovskite solar cells (CPSC). Background Art

[0002] Carbon electrode perovskite solar cells (CPSCs) are known for their excellent stability and low cost. Due to continuous efforts in the optimization of perovskite active layers and related interfaces, the photoelectric conversion efficiency (PCE) has increased from 6% 10 years ago to more than 20% today. In 2024, Professor Han Hongwei's team achieved a PCE of up to 22.2% in hole-free, printable mesoscopic CPSCs (meso-CPSCs) (Liu et al., Science 383, 1198–1204 (2024)), catching up with the pace of metal-based PSCs. However, mesoscopic CPSCs (Han's cells) are mainly prepared under relatively high temperature processes (~450°C), which not only increases production costs in industrial preparation, but also prolongs the production cycle.

[0003] In order to more effectively reduce costs and facilitate industrial production, Shi Tingting et al. realized the low-temperature preparation process of meso-CPSC in 2020 (Shi et al., Appl. Phys. Lett. 117(16), 163501(2020).), but the PCE has grown slowly in the past few years. Therefore, further improving the PCE of low-temperature meso-CPSCs remains an urgent task.

[0004] Due to the complex structure of the three-layer mesoporous skeleton, the crystallization process of PVSK in mesoporous CPSCs is quite complicated compared with other types of PSCs. By comparing the thickness of the three-layer mesoporous membrane of the device with different thicknesses, it can be found that in the mesoporous skeleton, the thickness of CE (~15μm or greater thickness) is much higher than that of the mesoporous ZrO2 layer (~2μm) or the mesoporous TiO2 layer (0.5~1.5μm). CE accounts for about 70% of the total mesoporous film volume. Therefore, more attention needs to be paid to the role of mesoporous CE in the crystallization process of PVSK. The shape and size of the carbon material in CE will also affect the crystallization process. However, the conductive material of the carbon layer of all carbon electrodes such as CN117082877A is one or more of micron-sized graphite, nano-sized carbon black particles, graphene or carbon nanotubes. The carbon layer of this technology is densely stacked, and the carbon black exists in the form of small nanoparticles. The preparation process of carbon black particles prepared separately is also cumbersome, and they are all nano-sized particles. However, the unfired mesoporous carbon film in low-temperature mesoporous carbon-based devices is difficult to form effective pores as permeation channels for the perovskite precursor solution.

[0005] In summary, in the original carbon black preparation process, there is no carbon black particle that can meet the pore size requirements of the low-temperature mesoporous carbon electrode. In addition, the existing low-temperature mesoporous carbon electrode is relatively dense and difficult to meet the penetration requirements of the device. Summary of the invention

[0006] In view of the problems existing in the existing low-temperature mesoporous CPSC, the first purpose of the present invention is to provide a graphite-micron-sized carbon black ball composite carbon slurry (also referred to as carbon slurry in the present invention) suitable for low-temperature preparation of mesoporous CPSC, aiming to prepare carbon slurry suitable for preparing carbon layers of mesoporous CPSC by low-temperature process.

[0007] The second object of the present invention is to provide a graphite-micron-sized carbon black ball composite carbon slurry prepared by the preparation method, a carbon electrode layer formed by curing, and use thereof in the preparation of mesoporous CPSC.

[0008] The third object of the present invention is to provide a mesoporous CPSC comprising the electrode layer and a low-temperature preparation method thereof.

[0009] The existing commercial carbon black is small in size and difficult to be used for low-temperature preparation of mesoporous CPSC. To address this problem, the present invention provides a carbon slurry and carbon electrode technology suitable for low-temperature preparation of mesoporous CPSC, specifically:

[0010] The preparation method of graphite-micron-sized carbon black ball composite carbon slurry comprises ball milling a solution system consisting of nano-sized carbon black, micron-sized graphite flakes and a solvent to obtain a carbon slurry composited with graphite-micron-sized carbon black balls;

[0011] Wherein, the weight ratio of the micron-sized graphite flakes to the nano-sized carbon black is 1 to 4:1;

[0012] The size of the micron-scale graphite flakes is between 10 and 50 μm;

[0013] The solvent is a solvent containing C1-C4 monoalcohol or water;

[0014] The ball milling time is more than 10 hours.

[0015] The present invention innovatively ball-mills nano-scale carbon black particles and micron-scale graphite flakes. Carbon black forms carbon black clusters under the extrusion of ball-milling media (balls); carbon black clusters undergo continuous multi-dimensional rotation under the shear force of adjacent graphite flakes. The synergistic effect of ball-milling media and graphite flakes causes nano-scale carbon black particles to form micron-scale carbon black balls. Further, by jointly controlling the size and ratio of micron-scale graphite flakes and nano-scale carbon black particles, as well as parameters such as solvent and ball-milling time, micron-scale carbon black balls that meet the application requirements of CPSC are obtained. In addition, the interface relationship between carbon black particles and graphite layers can be improved, so that a mesoporous three-dimensional carbon electrode layer that is suitable for mesoporous CPSC can be simply constructed under low temperature conditions, and its PCE and other properties can be improved.

[0016] In the present invention, the combined ball milling of nano-scale carbon black and micron-scale graphite sheets and the combined control of other parameters are the key to promoting the agglomeration of carbon black particles into a spherical structure and improving the composite interface morphology between the carbon black particles and the graphite sheets, thereby improving the performance of the mesoporous CPSC prepared at low temperature.

[0017] In the present invention, the D50 of the nano-scale carbon black is 20 to 100 nm; further, it can be 40 to 60 nm.

[0018] In the present invention, the plane size of the micron-scale graphite sheet is 20 to 35 μm; further, it can be 29 to 31 μm.

[0019] In the present invention, the solvent is at least one solvent selected from the group consisting of methanol, ethanol, isopropanol and water.

[0020] In the present invention, the material-liquid ratio in the ball milling stage is 0.1-0.2 g / mL.

[0021] In the present invention, the rotation speed of the ball mill is 200-300 r / min.

[0022] In the present invention, the ball milling time is 10 to 30 hours.

[0023] The invention also provides a graphite-micron-sized carbon black ball composite carbon slurry prepared by the preparation method.

[0024] In the present invention, based on the preparation method, carbon black and graphite can be given a special physical and chemical structure, and the carbon slurry prepared by the preparation method can unexpectedly construct a carbon electrode layer suitable for mesoporous CPSC at low temperature, which can improve its PCE and other properties.

[0025] The present invention also provides an application of the graphite-micron-sized carbon black ball composite carbon slurry in preparing mesoporous CPSC at low temperature.

[0026] Preferably, the low-temperature preparation refers to the temperature in the stage of preparing the mesoporous CPSC being below 150°C; further, it may be 100-150°C.

[0027] The present invention also provides a carbon electrode layer suitable for mesoporous CPSC, which is obtained by desolventizing the graphite-micron-sized carbon black ball composite carbon slurry obtained by the preparation method of the present invention.

[0028] The carbon electrode layer prepared by the preparation method of the present invention has more and more staggered graphite sheets, with obvious interlayer pores. Increasingly large micron-sized carbon black balls are buried in the interlayer pores, playing a role in supporting the graphite sheets, forming more pores and more interconnected permeation channels.

[0029] In the present invention, the carbon electrode layer suitable for mesoporous CPSC may also contain a binder. Further, the binder may include an inorganic binder, and further may be a zirconium oxide binder.

[0030] The carbon electrode layer of the present invention can be prepared by applying the carbon paste by scraping or screen printing and then drying. In addition, a binder can be added to the carbon paste, followed by scraping or screen printing and drying. The drying temperature can be below 150°C.

[0031] The present invention also provides a mesoporous CPSC, comprising a transparent conductive substrate, a dense electron transport material layer, a mesoporous electron transport material layer, a mesoporous barrier material layer and a carbon electrode layer, which are composited in sequence; wherein the carbon electrode layer is the carbon electrode layer; at least one of the carbon electrode layer, the electron transport material layer and the barrier material layer also contains perovskite and its precursor material.

[0032] In the present invention, the transparent conductive substrate is at least one of conductive substrates such as FTO glass, ITO glass or flexible PEN.

[0033] In the present invention, the electron transport material layer includes at least one material selected from SnO2, TiO2, ZnO and the like.

[0034] In the present invention, the barrier material layer includes at least one of ZrO2 and Al2O3.

[0035] In the present invention, the thickness of the transparent conductive substrate is 150-550nm, the thickness of the dense electron transport material layer is 30-50nm, the thickness of the mesoporous electron transport material layer is 0.5-1.5μm, the thickness of the mesoporous barrier material layer is 1.5-2.5μm, and the thickness of the carbon electrode layer is 15-25μm.

[0036] Preferably, the perovskite material is an organic-inorganic hybrid lead halide perovskite material, and its molecular formula is abbreviated as ABX3, wherein A is selected from one or more combinations of methylamine ion, formamidine ion, cesium ion, and 5-aminovalerate ion; B is a metal cation, selected from one or more combinations of lead ion and tin ion; X is a halogen ion, selected from one or more combinations of chlorine, bromine, and iodine. For example, it can be at least one of iodine lead methylamine, iodine lead formamidine, etc.

[0037] The present invention also provides a low-temperature preparation method of the mesoporous CPSC, wherein each layer of material is compounded in sequence according to the hierarchical structure of the mesoporous CPSC, and then a perovskite precursor material solution is injected, dried and crystallized to form a perovskite material; wherein the annealing temperature of each layer of material compounding stage and the temperature of the perovskite precursor material solution drying and crystallization stage are both below 150°C.

[0038] Beneficial Effects

[0039] The present invention innovatively conducts synergistic ball milling of nano-scale carbon black and micron-scale graphite flakes, and further coordinates the joint control of parameters such as size, ratio, solvent and time of the two, which can unexpectedly achieve synergy and obtain micron-scale carbon black balls that meet the application requirements of CPSC. In addition, it can also improve the interface relationship between carbon black particles and graphite layers, so that a mesoporous three-dimensional carbon electrode layer that is suitable for mesoporous CPSC can be simply constructed under low temperature conditions, and its PCE and other properties can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 SEM image of carbon slurry obtained in Example 1 (×30k);

[0041] Figure 2 SEM image of carbon slurry obtained in Example 1 (×20k);

[0042] Figure 3 SEM image of carbon slurry obtained in Example 1 (×5k);

[0043] Figure 4 The SEM image (×5k) of the coating formed by the carbon slurry in Example 1;

[0044] Figure 5 The SEM image (×10k) of the coating formed by the carbon slurry in Example 1;

[0045] Figure 6 This is the pore size distribution diagram of the carbon slurry obtained in Example 1;

[0046] Figure 7 Schematic diagram of preparing mesoporous CPSC in Example 1;

[0047] Figure 8 This is a cross-sectional SEM image of the three-layer mesoporous structure of the device obtained in Example 1 (×5k);

[0048] Fig. 9 This is a cross-sectional SEM image of the three-layer mesoporous structure of the device obtained in Example 1 (×50k);

[0049] Fig.10 is a graph of the photocurrent-voltage curve of the device obtained in Example 1;

[0050] Fig.11 This is the SEM image of the carbon slurry obtained in Example 2A;

[0051] Fig.12 This is the SEM image of the carbon slurry obtained in Example 2B;

[0052] Fig.13 The SEM image of the carbon slurry prepared for Comparative Example 1;

[0053] Fig.14 The SEM image of the carbon slurry prepared for Comparative Example 2;

[0054] Fig.15 The SEM image of the carbon slurry prepared for Comparative Example 3;

[0055] Fig.16 The SEM image of carbon slurry prepared for Comparative Example 5;

[0056] Fig.17 The pore size distribution diagram of the carbon slurry prepared for Comparative Example 6. DETAILED DESCRIPTION

[0057] The graphite size is the size of its flakes. The carbon black size is the D50 size.

[0058] In the present invention, the SEM of the carbon slurry is performed by coating the carbon slurry to form a coating and then performing a SEM scanning test.

[0059] The thickness of the carbon coating in the photoelectric conversion efficiency test stage is the same.

[0060] Part I: Preparation of Carbon Slurry

[0061] Example 1

[0062] Step 1:

[0063] Weigh 2g of 30μm graphite and 0.5g of 50nm carbon black and add them into a ball mill. Continue to add 20ml of ethanol and mix them. Then, mill them in a ball mill at 250r / min for 24h to obtain a composite carbon slurry.

[0064] Step 2:

[0065] According to the solvent volume ratio of ethanol: ZrO2 colloidal binder = 4:1, 5 ml of ZrO2 colloidal binder (0.0375 g / ml ZrO2 nanocrystals / ethanol) was added to the semi-finished carbon slurry after ball milling, and stirred thoroughly to obtain the finished low-temperature carbon slurry. The surface SEM image (scanning electron microscope image) of the carbon slurry is shown in the attached figure. Figure 1 , 2, 3, it can be clearly observed that micron-sized carbon black balls of about 6 μm are formed. The carbon slurry is coated to form a carbon electrode layer, and its cross-sectional SEM image is shown in the attached figure. Figure 4 , 5. It can be observed that the carbon electrode layer prepared by the preparation method of the present invention has more and more staggered graphite sheets, with obvious interlayer pores. Increasingly large micron-sized carbon black balls are buried in the interlayer pores, playing a role in supporting the graphite sheets and forming more pores and more interconnected permeation channels. The pore size distribution diagram of the carbon slurry is shown in the attached figure. Figure 6 , a higher porosity can be obtained.

[0066] Step 3: Deposit a dense electron transport layer (SnO2, 50nm thick) and a mesoporous electron transport layer (TiO2, about 1μm thick) on fluorine-doped SnO2 conductive glass (FTO). Each layer is annealed at 150°C for 1h. Then a mesoporous barrier layer (ZrO2, 2μm thick) is deposited again on the mesoporous electron transport layer. Carbon electrode (prepared by scraping the low-temperature carbon slurry in step 2, with a thickness of about 20μm), each layer is annealed at 150°C for 1h and 5h respectively. The schematic diagram of the device structure is shown in the attached figure. Figure 7 The cross-sectional SEM images are shown in the attached Figure 8 .

[0067] Step 4: Filling the perovskite photoactive layer: Take 20 μL of iodine lead methylamine (CH3NH3PbI3) precursor solution and drop it on the carbon electrode. After standing for 10 minutes, place it in a vacuum drying oven (set the pressure inside the box to negative pressure and the temperature to 50°C), and vacuum anneal for 3 hours to obtain a simple structure of mesoporous carbon-based perovskite solar cells; its cross-sectional SEM image is shown in the attached figure. Fig. 9 .

[0068] The preparation method of CH3NH3PbI3 is as follows: weigh 0.3975g of iodine methylamine (CH3NH3I, MAI), 1.146g of lead iodide (PbI2), and 0.03g of 5-aminovaleric acid iodide (HOOC(CH2)4NH3I, 5AVA-I) in a bottle. Add 2.7mL of γ-butyrolactone (GBL) and stir with a magnetic stirrer at 60-70℃ for 6-7h to obtain a perovskite precursor solution.

[0069] After the all-low-temperature mesoporous carbon-based perovskite solar cell device with micron-sized carbon black spherical carbon electrodes was prepared, the -2 The photocurrent-voltage curve was tested under simulated sunlight ( Fig.10 ), and achieved a photoelectric conversion efficiency of 15.88%.

[0070] Example 2 - Ratio Screening Case

[0071] Compared with Example 1, the only difference is that the ratio of graphite / carbon black is changed by changing the weight of carbon black. The experimental groups are:

[0072] Group A: The amount of carbon black was 0.75 g, and the weight ratio of graphite / carbon black was 2.67:1;

[0073] Group B: The amount of carbon black was 1 g, and the weight ratio of graphite / carbon black was 2:1;

[0074] SEM of groups A and B are shown in Fig.11 and Fig.12, micron-sized carbon black balls were obtained in the carbon slurry. The test was carried out in the same manner as in Example 1, and the results were as follows:

[0075] Group A: Photoelectric conversion efficiency is 15.04%;

[0076] Group B: The photoelectric conversion efficiency is 15.20%.

[0077] Example 3

[0078] Compared with Example 1, the only difference is that the type and amount of solvent are changed. The experimental groups are:

[0079] Group A: the solvent was isopropanol, the liquid-to-solid ratio before ball milling was 10 mL / g, and other operations and parameters were the same as those in Example 1. The carbon black in the carbon slurry after ball milling formed micrometer-sized carbon black balls, and the photoelectric conversion efficiency was 15.30%.

[0080] Group B: The solvent was methanol, the liquid-to-solid ratio before ball milling was 12 mL / g, and other operations and parameters were the same as those in Example 1. The carbon black in the carbon slurry after ball milling formed micrometer-sized carbon black balls, and the photoelectric conversion efficiency was 15.19%.

[0081] Group C: The solvent was water, the liquid-to-solid ratio before ball milling was 15 mL / g, and other operations and parameters were the same as those in Example 1. The carbon black in the carbon slurry after ball milling formed micron-sized carbon black balls, and the photoelectric conversion efficiency was 15.11%.

[0082] Example 4

[0083] Compared with Example 1, the only difference is that the ball milling speed and time are changed. The experimental groups are:

[0084] Group A: The ball milling speed was 300 r / min, the ball milling time was 30 h, and other operations and parameters were the same as those in Example 1. The carbon black in the carbon slurry after ball milling formed micron-sized carbon black balls, and the photoelectric conversion efficiency was 15.65%.

[0085] Group B: The ball milling speed was 200 r / min, the ball milling time was 40 h, and other operations and parameters were the same as those in Example 1. The carbon black in the carbon slurry after ball milling formed micron-sized carbon black balls, and the photoelectric conversion efficiency was 15.54%.

[0086] Example 5

[0087] Compared with Example 1, the only difference is that the size of the graphite sheet and the size of the carbon black are changed. The experimental groups are:

[0088] Group A: The size of graphite flakes was 20 μm, the size of carbon black was 40 nm, and other operations and parameters were the same as those in Example 1. The carbon black in the carbon slurry after ball milling formed micrometer-sized carbon black balls, and the photoelectric conversion efficiency was 15.01%.

[0089] Group B: The graphite flake size is 35 μm, the carbon black size is 60 nm, and other operations and parameters are the same as those in Example 1. The carbon black in the carbon slurry after ball milling forms micrometer-sized carbon black balls, and the photoelectric conversion efficiency is 15.74%.

[0090] Comparative Example 1

[0091] Compared with Example 1, the only difference is that cellulose is also added to the ball milling system. The steps are: weigh 2 g of 3 μm-sized graphite and 50 nm-sized carbon black ( Figure 1 ) 0.5g, 1g cellulose were added to the ball mill. 20ml ethanol was added to the mixture and then ball milled in a ball mill at 250r / min for 24h to obtain a composite carbon slurry. The SEM of the carbon slurry after forming a coating is shown in the attached figure. Fig.13 There are only granular carbon black on the surface of the carbon electrode, and no micron-sized carbon black balls. The carbon layer has insufficient pores, which limits the filling of the perovskite photoactive layer, and the photoelectric conversion efficiency is 3.02%.

[0092] Comparative Example 2

[0093] Compared with Example 1, the only difference is that no graphite is added, but 50nm size carbon black ( Figure 1 ) 0.5g was added to the ball mill. 20ml of ethanol was added to the mixture and then ball milled in a ball mill at 250r / min for 24h to obtain a composite carbon slurry. Fig.14 Due to the lack of synergistic effect of graphite flake shear force, carbon black ball milling alone cannot form micron-sized carbon black balls, and the carbon layer has insufficient pores, which limits the filling of the perovskite photoactive layer, and the photoelectric conversion efficiency is 1.01%.

[0094] Comparative Example 3

[0095] Compared with Example 1, the only difference is that the graphite is replaced with 3 μm size graphite in equal amount, and the other operations and parameters are the same as those in Example 1. Fig.15 ,Since 3μm-sized graphite flakes cannot generate enough shear force, micron-sized carbon black balls cannot be formed. The photoelectric conversion efficiency is 11.04%.

[0096] Comparative Example 4

[0097] Compared with Example 1, the only difference is that the carbon slurry is not subjected to the ball milling treatment, but the carbon slurry in which the graphite and carbon black are directly dispersed cannot be subjected to the extrusion of the ball milling medium balls and the shearing effect of the graphite sheets under this extrusion, so it is difficult to form micron-sized carbon black balls, and the photoelectric conversion efficiency is 8.14%.

[0098] Comparative Example 5

[0099] Compared with Example 1, the only difference is that the ball milling time is 4 hours, and the other operations and parameters are the same as those in Example 1. Fig.16 However, due to the short synergistic effect time, micron-sized carbon black balls cannot be formed. The photoelectric conversion efficiency is 9.45%.

[0100] Comparative Example 6

[0101] Compared with Example 1, the only difference is that the ratio of graphite to carbon black is changed by changing the mass of carbon black, the amount of carbon black is 0.125 g, and the weight ratio of graphite to carbon black is 16:1; other operations and parameters are the same as Example 1. Due to the low mass of carbon black, sufficient clusters cannot be formed, and thus micron-sized carbon black balls cannot be formed. Fig.17 , the porosity is low, resulting in insufficient pores in the carbon layer, limiting the filling of perovskite, and the photoelectric conversion efficiency is 6.55%.

Claims

1. A method for preparing a graphite-micron-sized carbon black ball composite carbon slurry, characterized in that: A solution system consisting of nano-scale carbon black, micron-scale graphite flakes and a solvent is subjected to ball milling treatment to obtain a carbon slurry composited with graphite-micron-scale carbon black balls; Wherein, the weight ratio of the micron-sized graphite flakes to the nano-sized carbon black is 1 to 4:1; The size of the micron-scale graphite flakes is between 10 and 50 μm; The solvent is a solvent containing C1-C4 monoalcohol or water; The ball milling time is more than 10 to 40 hours.

2. The preparation method according to claim 1, characterized in that The D50 of the nano-scale carbon black is 20 to 100 nm; further, it can be 40 to 60 nm; Preferably, the plane size of the micron-sized graphite flakes is 25 to 35 μm.

3. The preparation method according to claim 1, characterized in that: The solvent is at least one of methanol, ethanol, isopropanol and water; Preferably, the material-liquid ratio in the ball milling stage is 0.1-0.2 g / mL.

4. The preparation method according to claim 1, characterized in that: The speed of the ball mill is 200-300r / min; Preferably, the ball milling time is 10 to 30 hours.

5. A graphite-micron-sized carbon black ball composite carbon slurry prepared by the preparation method according to any one of claims 1 to 4.

6. Use of the graphite-micron-sized carbon black ball composite carbon slurry prepared by the preparation method according to any one of claims 1 to 4 for low-temperature preparation of mesoporous CPSC; Preferably, the low-temperature preparation refers to the temperature in the stage of preparing the mesoporous CPSC being below 150°C; further, it may be 100-150°C.

7. A carbon electrode layer suitable for mesoporous CPSC, characterized in that: The method is obtained by desolventizing the graphite-micron-sized carbon black ball composite carbon slurry prepared by the preparation method according to any one of claims 1 to 4.

8. The carbon electrode layer suitable for mesoporous CPSC according to claim 7, characterized in that: Also includes a binder; Preferably, the binder comprises an inorganic binder, preferably a zirconia binder.

9. A mesoporous CPSC, characterized in that: It comprises a transparent conductive substrate, a dense electron transport material layer, a mesoporous electron transport material layer, a mesoporous barrier material layer and a carbon electrode layer which are composited in sequence; wherein the carbon electrode layer is the carbon electrode layer according to claim 7 or 8; the carbon electrode layer, the mesoporous electron transport material layer and the mesoporous barrier material layer are filled with perovskite and its precursor material; Preferably, the transparent conductive substrate is at least one of FTO glass, ITO glass, or flexible PEN and other conductive substrates; Preferably, the electron transport material layer includes at least one material selected from SnO2, TiO2, ZnO, etc.; Preferably, the barrier material layer includes at least one of ZrO2 and Al2O3; Preferably, the thickness of the transparent conductive substrate is 150-550 nm, the thickness of the dense electron transport material layer is 30-50 nm, the thickness of the mesoporous electron transport material layer is 0.5-1.5 μm, the thickness of the mesoporous barrier material layer is 1.5-2.5 μm, and the thickness of the carbon electrode layer is 15-25 μm; Preferably, the perovskite material is an organic-inorganic hybrid lead halide perovskite material, whose molecular formula is abbreviated as ABX3, wherein A is selected from one or more combinations of methylamine ion, formamidine ion, cesium ion, and 5-aminovaleric acid anion; B is a metal cation, selected from one or more combinations of lead ion and tin ion; X is a halogen ion, selected from one or more combinations of chlorine, bromine, and iodine.

10. A low-temperature preparation method of mesoporous CPSC according to claim 9, characterized in that: The layers of materials are compounded in sequence according to the hierarchical structure of the mesoporous CPSC, and then a perovskite precursor material solution is injected, dried and crystallized to form a perovskite material; wherein the annealing temperature of the compounding stage of each layer of materials and the temperature of the perovskite precursor material solution drying and crystallization stage are both below 150°C.

Citation Information

Patent Citations

  • Perovskite solar cell based on lead-absorbing carbon electrode and preparation method

    CN117082877A